Assessing climate change impacts on water footprint of crop production and crop yield: a case study of the Wu River basin, Taiwan - Guan-Zhou Lin; Li-Chi Chiang (Ecological Indicators, 2025)
Evaluating the water footprint of crop production is crucial for achieving sustainable agriculture and efficient water resource allocation in the watershed, particularly in the context of climate change. This study leverages the SWAT model and AR5 climate scenario data to simulate crop water consumption, grey water demand, and crop yield variations under the RCP8.5 scenario for the late 21st century in the Wu River basin, Taiwan. The findings reveal a 1–7% decrease in blue-green water consumption, alongside a significant increase in grey water demand (33–63% for nitrate nitrogen and 68–113% for total phosphorus). Variation in rainfall patterns impact blue-green water consumption and directly affect crop yields, with projected reductions averaging 18% for rice, 41% for sweet potatoes, and 45% for oranges. The blue-green water footprint of paddy fields in the region is already six times the global average and 1.8 times that of irrigated regions worldwide. Under climate change scenarios, the blue-green water footprints of rice, sweet potatoes, and oranges are projected to increase by 122%, 154%, and 196%, respectively. This research highlights sustainable agricultural practices for Taiwan and beyond, emphasizing the need to address rising nutrient grey water demand from extreme rainfall. It recommends alternative crops or reduced phosphorus fertilizer use to mitigate agriculture’s environmental impact, ensuring sustainable development in the Wu River basin and similar regions globally.